Phytochemical Profile and Antioxidant Properties of Bee-Collected Artichoke (Cynara scolymus) Pollen - Aleksandar Ž. Kostić; Danijel D. Milinčić; Nebojša Nedić; Uroš M. Gašić; Bojana Špirović Trifunović; Denis Vojt; Živoslav Lj. Tešić; Mirjana B. Pešić (MDPI AG, 2021)
The current study intended to determine, for the first time, phenolic and fatty acid profile, antioxidant and certain nutritional properties of monofloral bee-collected artichoke (Cynara scolymus) pollen. Based on UHPLC-DAD MS-MS analysis the main phenolics in extractable fraction were different flavonol glycosides (in particular Isorhamnetin-3-O-glucoside, 49.2 mg/kg of dry weight) while ferulic acid was the predominant phenolic compound (39.4 mg/kg of dry weight) in the alkaline hydrolyzable fraction. Among fatty acids (FAs), results of GC-FID analysis revealed prevalence of unsaturated FAs with cis-5,8,11,14,17-eicosapentaenoic acid (EPA) and oleic acid as the main ones- 28.4% and 24.9%, respectively. Based on the FA composition, nutritional analysis proved that artichoke bee-collected pollen had balanced ω-6 and ω-3 FAs content. To determine the antioxidant properties of pollen, five different assays were applied. It was proved that bioactive compounds in artichoke pollen possessed significant ability to quench DPPH radical as well as ABTS radical cation. In addition, in vitro phosphomolybdenum assay confirmed that artichoke pollen is an excellent source of different antioxidants. Pollen extracts exhibited moderate ferric reducing power as well as low ferrous chelating ability. Some further antioxidant studies (preferably in vivo) should be performed to confirm the observed results.